A computational model of force within the ligaments and tendons in progressive collapsing foot deformity. Issue 2 (2nd June 2022) - Malakoutikhah, Hamed; Madenci, Erdogan; Latt, Leonard Daniel
Abstract: Progressive collapsing foot deformity results from degeneration of the ligaments and posterior tibial tendon (PTT). Our understanding of the relationship between their failures remains incomplete. We sought to improve this understanding through computational modeling of the forces in these soft tissues. The impact of PTT and ligament failures on force changes in the remaining ligaments was investigated by quantifying ligament force changes during simulated ligament and tendon cutting in a validated finite element model of the foot. The ability of the PTT to restore foot alignment was also evaluated by increasing the PTT force in a foot with attenuated ligaments and comparing the alignment angles to the intact foot. We found that failure of any one of the ligaments led to overloading the remaining ligaments, except for the plantar naviculocuneiform, first plantar tarsometatarsal, and spring ligaments, where removing one led to unloading the other two. The combined attenuation of the plantar fascia, long plantar, short plantar, and spring ligaments significantly overloaded the deltoid and talocalcaneal ligaments. Isolated PTT rupture had no effect on foot alignment but did increase the force in the deltoid and spring ligaments. Moreover, increasing the force within the PTT to 30% of body weight was effective at restoring foot alignment during quiet stance, primarily through reducing hindfoot valgus and forefoot abduction as opposed to improving arch collapse. Our findings suggest that early intervention might be used to prevent the progression of deformity. Moreover, strengthening the PTT through therapeutic exercise might improve its ability to restore foot alignment.